Cervical Cancer Risk Prediction with Machine Learning: Analysis of Cervical Cancer Risk Classification Dataset - Paripurna, Yoga; Budiono, Irwan (Sekolah Tinggi Ilmu Kesehatan Kendal, 2025)
Cervical cancer remains one of the leading causes of cancer death in women, especially in developing countries. Early detection through screening is essential to reduce morbidity and mortality, but the main challenge is to identify individuals at high risk efficiently. This study aims to build a machine learning prediction model to classify cervical cancer biopsy results based on available risk factors. Objectives: This study aims to build a cervical cancer risk prediction model using a machine learning algorithm based on available risk factors. The public dataset